PENINGKATAN PROFESIONAL SDM MELALUI PROGRAM PENGEMBANGAN: SUATU PERSPEKTIF BERDASARKAN SUMBER DAYA MANUSIA - SU, Setyaningsih (Universitas Slamet Riyadi, 2006)
ABSTRACT Human recources development is need strategic action by substantive important human recources development is good governance that change paradigm, attitude, value and behavior.Are development hope officers increase insight, that attitude and behavior, and soon officers are individual. Officers are ripe and need value is good and they are soon perceptive that challenge to organization or development change growth organization that become upgrade professional work.Development that process educational hope can increase insight, value change and growth behavior become increase professional, efficiency and effectiveness. Keywords: Human recources development, good governance, professional officers, efficiency, effectiveness